Sign language to speech conversion - del Carpio Salinas, Jorge Alberto (2007)
This work uses the image processing methods and neural network to classify the sign language patterns, a set of function had been implemented in Matlab to achieve our goal. Our vocabulary of sign language are composed of 24 letters belong to the alphabet, this work considers only those gestures without movement, our hardware are a digital camera and a PC.